ORMUB: extensão universitária incentivando ações na comunidade interna e externa - Locci, Valter [UNESP]; Marques, Emília de Mendonça Rosa [UNESP]; Cruz, Luiz Francisco da [UNESP]; Lázaro, Cristiane Alexandra [UNESP]; Boato, Luis Felipe Salvador [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Mathematic's Regional Olympiad of UNESP in Bauru (ORMUB) has been held by 22 years by the Department of Mathematics, Faculty of Science. This work is a brief description of your organization and points out some reflections of their influence on internal and external community.

Após 22 anos de realização da Olimpíada Regional de Matemática da UNESP de Bauru (ORMUB) pelo Departamento de Matemática da Faculdade de Ciências da UNESP, este trabalho faz um breve relato de sua organização e aponta alguns reflexos de sua influência na comunidade interna e externa ao câmpus.
Keywords: Olympics; Mathematics; Problem-solving; Olimpíada; Matemática; Resolução de problemas